Numerical Investigation Of Nanofluids Flow and Heat Transfer in 90 Elbow With square Cross-Section - Farsani, Ayoob Khosravi; Nodooshan, Afshin Ahmadi (Ciência e Natura, 2015)
In this article, forced convective heat transfer of nanofluid flow in a horizontal tube with a square cross-section and 90-degree elbow under heat flux was investigated in a numerical method. The homogeneous nanofluid of aluminum oxide and water (Al2O3) was used as the working fluid. For the numerical solution of continuity, momentum and energy equations, the finite volume method was used. In this study, the effect of Reynolds number and the solid volume fraction and the impact of the elbow on the flow field and the heat transfer rate and pressure drop was investigated. The results were presented in the form of flow and temperature contours and the Nusselt diagrams, which have a good relation with the experimental results, and showed that by increasing the solid volume fraction and Reynolds number, the heat transfer in the elbow increases. Also the concave surface from inside the tubes had a greater impact on heat transfer than the convex surface.